TEACHER PROBLEMATICS IN IMPLEMENTING THE INDEPENDENT LEARNING CURRICULUM IN SCIENCE LEARNING IN CLASS 4 MIS MIFTAHUL KHOIR AS A REVIEW OF ISLAMIC EDUCATION - Muhammad Basarrudin (Progresif : Media Publikasi Ilmiah, 2024)
MIS Miftahul Khoir Rasau Jaya has implemented the Independent Learning Curriculum, despite the various problems that exist. It is still being implemented in stages, despite planning, implementation and assessment issues. Therefore, the aim of this research is to find out the problems teachers face when implementing the independent learning curriculum in science and science learning in class 4 of MIS Miftahul Khoir Rasau Jaya as a review of Islamic education. In this research, a qualitative approach is used, and the type of research is descriptive. The principal, teachers and 4th grade students were the research subjects. Data was collected through observation, interviews and documentation. Data analysis was carried out through reduction, presentation and drawing conclusions. The results of the research show that teachers at MIS Miftahul Khoir Rasau Jaya face problems in implementing the Independent Learning Curriculum in planning, implementing and assessing science and science learning. Problems include analyzing CP, formulating TP, compiling ATP and teaching modules, determining learning methods and strategies, limited student books, lack of ability and readiness to use learning methods and media, and teaching materials. Various ideas from Merdeka Belajar have been implemented at MIS Miftahul Khoir Rasau Jaya, such as creating learning planning administration even though it is still made in groups, using class projects and school projects, and implementing the Pancasila Student Profile, although it still needs improvement and development. This is necessary to achieve the objectives of the Independent Learning Curriculum.